Role of Oral Steroids in The Treatment of Carpal Tunnel Syndrome - Ahmad, Zaheer; Aslam, Muhammad Adnan; Hasan, Arsilan (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the efficacy of oral steroids and intracarpal steroids in treating carpal tunnel syndrome.Study Design: Quasi-experimental study.Place and Duration of Study: Neurology department, Allied Hospital, Faisalabad Pakistan, from Jul to Dec 2020.Methodology: Patients of either gender, >18 years of age having carpal tunnel syndrome were included and divided into two groups. The oral steroids group received 20mg Prednisone tablets for two weeks and 2cc 0.9% Saline injection locally in the carpal tunnel on the affected hand by a neurologist. Intracarpal steroids group received 40mg Methylprednisolone locally in the carpal tunnel on the affected hand and placebo tablets for two weeks. Global symptom score was calculated at baseline and four weeks of treatment. Nerve conduction studies were conducted at baseline and four weeks of treatment.Result: A total of 106 patients were included in the study. There was a statistically significant improvement in the oral steroids group and intracarpal steroids group at four weeks follow up in mean sensory conduction velocity, mean global symptom score, mean motor conduction velocity and mean sensory latency (p